Randomized Clinical Trial for Comparison of Drain Versus no Drain Thyroidectomy - Muhammad Azam Arif, Farhan Shahzad, Adeel Ali Tahir, Muhammad Yasir Naseem (Pakistan Journal of Medical & Health Sciences, 2022)
Drains have been traditionally used routinely after thyroidectomy despite limited evidence to suggest any benefit. In many facilities, drains are routinely inserted after thyroidectomy with the aim of preventing hematoma formation and accumulation of seroma. Objective: To compare the outcome of drain versus no drain after thyroidectomy in patients presenting with clinically benign lesions of thyroid Methods: Study design is Randomized control trail. Settings are Department of Surgery, Mayo University Hospital Ireland. Study was completed in 6 months after the approval of synopsis 13-07-2015 to 31-05-2016. After taking approval from Hospital Ethical Committee, 60 patients fulfilling the inclusion criteria were selected from ward of Department of Surgery, Mayo University Hospital Ireland. Informed consent was taken. The demographic information was obtained. Patients were randomly divided in two groups by using lottery method. In group A, drain was inserted after surgery while in group B, no drain was inserted. All surgeries were done by a single surgical team. After surgery patients were shifted to ward and were followed-up there. At time of discharge, duration of hospital stay was noted. Patients were advised to follow-up in OPD after 7 days of surgery. Patients were assessed for seroma and hematoma formation. Results: Mean age of women in Group-A and in Group-B was 43.73±10.51 years and 40.23±9.07 years. In Group-A there were 13(43.3%) male and 17(56.7%) females while in Group-B there were 18(60%) male and 12(40%) females. In Group-A mean hospital stay of patients was 5.80±1.42 days and in Group-B mean hospital stay of patients was 3.76±1.10 days. In Group-B patients rate of hematoma and seroma formation was low as compared to that of Group-A patients but this difference was not statistically significant. Conclusion: Outcome of thyroidectomy is better in terms of shorter hospital stay, and other post operative complications in patients without drain. Now the controversy is clear that thyroid surgery without drain results in good outcome for patients. So there is no beneficial aspect seen in patients with the use of drain after thyroidectomy.